Investigation of Room Attendant Service Quality and Guest Satisfaction in the Hospitality Industry - Pupus Atika Septiany; Mansur, Ahmad (International Journal of Educational and Life Sciences, 2024)
The hospitality sector relies on hotels for visitor lodgings and amenities. Housekeeping includes keeping guest rooms clean and comfortable. This research evaluates how Renaissance Okinawa Resort room attendants prepare rooms and guest satisfaction. For quantitative descriptive study, 100 resort visitors were surveyed. SERVQUAL scored service quality on assurance, tangibles, responsiveness, empathy, and reliability. Room attendants disappointed visitors by -0.20 generally. The assurance dimension differed most, whereas tangibles least. The survey also identified a 0.78 link between client happiness and room attendant service. The findings suggest regular guest satisfaction surveys, training, performance reviews, resource allocation, and education to enhance room attendant services. This research adds to the literature on room attendant service and client satisfaction in Japanese resort hotels.